PENGARUH QUALITY OF WORK LIFE, BUDAYA ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR TERHADAP KINERJA GURU PONDOK PESANTREN DI KOTA TANGERANG SELATAN - Lestari, Nanda Wida Lestari; Anwar, Saiful Anwar; Zubaidah, Siti Zubaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Quality of Work Life, organizational culture, and Organizational Citizenship Behaviour (OCB) on teacher performance in Islamic boarding schools in South Tangerang City. This research employs a quantitative approach with an associative method. The population consists of all active teachers in 2025, and the sample was determined using the Slovin formula, resulting in 106 respondents. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using multiple linear regression. The results show that Quality of Work Life, organizational culture, and Organizational Citizenship Behaviour partially and simultaneously have a positive and significant effect on teacher performance. Organizational Citizenship Behaviour is the most dominant variable, followed by organizational culture and Quality of Work Life. These findings indicate that teacher performance is not only determined by technical competence, but also by the quality of work life, the strength of organizational values, and teachers’ voluntary behavior. Therefore, improving teacher performance requires a comprehensive approach through strengthening these three aspects in a sustainable manner.